Pengaruh Motif Rasional Dan Motif Emosional Terhadap Keputusan Pembelian Konsumen Pada Supermarket Cemara Asri Pasar Buah Medan - Poppy Ananda; Teddi Pribadi; Haryaji Catur Putera Hasman; Isnaniah Laili Khatami (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2022)
This study aims to determine whether rational motives and emotional motives have a significant positive effect partially or simultaneously on consumer purchasing decisions at Cemara Astri Fruit Market Medan. The research was conducted using a questionnaire distributed to 91 samples consisting of consumers of the Cemara Asri Supermarket, Medan Fruit Market. This type of research is quantitative research with an associative approach, namely research that aims to determine whether there is an effect of the independent variable on the dependent variable. The data analysis technique used is multiple linear regression. The results obtained from this study are rational motives and emotional motives have a significant positive effect partially or simultaneously on consumer purchasing decisions at Cemara Asri Supermarket Medan Fruit Market.